Kajian Teologi Inkulturasi dalam Upacara Mendegger Uruk di Desa Penanggalan Binanga Boang Kabupaten Pakpak Bharat - Delila Bancin; Hanna Dewi Aritonang; Warseto Freddy Sihombing; Robert JT. Sitio; Grecetinovitria Butar-Butar (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
This study aims to examine the meaning of the Mendegger Uruk ceremony for the Pakpak community and explore the process of Inculturation Theology applied in the ceremony in Penanggalan Binanga Boang Village, Pakpak Bharat Regency. The method used is a qualitative method with a phenomenological approach. Data collection techniques are carried out through observation, interviews, and documentation. The data used consists of primary and secondary data. The research population includes traditional figures and cultural figures, with a sample of five people (four traditional figures and one cultural figure). The results of the study show that the Mendegger Uruk ceremony was initially carried out as a response to difficult situations, such as illness and social problems. However, with the entry of the Gospel teachings, inculturation occurred in this ceremony, where elements of ancestor worship were replaced with prayers and gratitude in accordance with Christian teachings. Theology of Gospel Inculturation, according to Emmanuel Martasudjita, is the process of the Church's adaptation to local culture, so that the Gospel message can be conveyed more relevantly and effectively. The Gospel does not erase local culture, but rather purifies elements that are not in accordance with Christian teachings.